Limpograss (Hemarthria altissima) Overview and Management - Yoana Newman; Joao Vendramini; Lynn E. Sollenberger; Ken Quesenberry (EDIS)
SS-AGR-320, an 8-page illustrated fact sheet by Yoana Newman, Joao Vendramini, Lynn E. Sollenberger, and Ken Quesenberry, describes this warm-season perennial grass that is well adapted to flatwoods sites in Florida — history and released cultivars, yield, nutritive values, animal performance, planting, management, utilization, and insects and plant diseases. Includes references. Published by the UF Department of Agronomy, August 2009.